Biology and therapy of multiple myeloma. Issue 8 (23rd April 2019) - Joshua, Douglas E; Bryant, Christian; Dix, Caroline; Gibson, John; Ho, Joy
Summary: Genetic sequencing of the myeloma genome has not revealed a specific disease‐determining genetic alteration. Multiple disease subclones exist at diagnosis and vary in clinical importance with time and drug sensitivity. New diagnostic criteria have identified indications for early introduction of therapy. Autologous stem cell transplantation remains an essential component of therapy in young and fit patients. The use of continual suppressive (maintenance) therapy has been established as an important component in therapy. Immune therapies and the harnessing of the innate immune system offer great promise for future treatments. Since 2005, quality of life, supportive therapies, and survival have dramatically improved over a decade of remarkable progress. The common manifestations of multiple myeloma, such as bone pain, fatigue and weight loss, may be non‐specific and are often initially ignored or missed by patients and medical practitioners.